2006
DOI: 10.1242/dev.02291
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of N-cadherin-mediated adhesion on the development of myotomal waves

Abstract: Myotomal fibers form by a first wave of pioneer myoblasts from the medial epithelial somite, and by a second wave from all four lips of the dermomyotome. Then, a third wave of mitotic progenitors colonizes the myotome, initially stemming from the extreme lips and, later, from the central dermomyotome sheet. In vitro studies have suggested that N-cadherin plays a role in myogenesis, but its role in vivo remains poorly understood. We find that during the growth phase of the dermomyotome sheet, when the orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 57 publications
4
48
1
Order By: Relevance
“…and C.K., unpublished). Consistent with these results, both cN390⌬-GFP and CBR-GFP have been shown to cause an initial loss of epithelial morphology in cells of the avian dermomyotome, yet they had opposite effects in driving cell segregation into dermal or myotomal domains, respectively (Cinnamon et al, 2006). These constructs also altered the morphology of epithelial cell lines (Fujimori and Takeichi, 1993), but, surprisingly, when misexpressed using an adenoviral approach, they had no effect on NT morphology (Nakagawa and Takeichi, 1998).…”
Section: Research Articlementioning
confidence: 82%
“…and C.K., unpublished). Consistent with these results, both cN390⌬-GFP and CBR-GFP have been shown to cause an initial loss of epithelial morphology in cells of the avian dermomyotome, yet they had opposite effects in driving cell segregation into dermal or myotomal domains, respectively (Cinnamon et al, 2006). These constructs also altered the morphology of epithelial cell lines (Fujimori and Takeichi, 1993), but, surprisingly, when misexpressed using an adenoviral approach, they had no effect on NT morphology (Nakagawa and Takeichi, 1998).…”
Section: Research Articlementioning
confidence: 82%
“…In the DM, one possible event that coincides in time with loss of Shh responsiveness is its conversion into mesenchyme, during which production of myotomal fibers is substituted by mitotic Pax7 + progenitors that are Shh-insensitive in both mice and avians. DM dissociation is triggered by myotomal fibroblast growth factor signaling (Delfini et al, 2009), and by loss of N-cadherin (cadherin 2), which also alters their apicobasal polarity (Ben-Yair et al, 2011;Cinnamon et al, 2006); the processes described above could alter the composition or organization of cilia responsible for signal transduction (Eggenschwiler and Anderson, 2007). Along this line, apically aligned cilia present in the epithelial DM change their distribution upon DM dissociation to become randomly localized on the cell surface (our unpublished data).…”
Section: Research Articlementioning
confidence: 91%
“…Studies in avians showed that around embryonic day (E) 2.5 the lips generate myocytes (Cinnamon et al, 2006;Cinnamon et al, 1999;Gros et al, 2004;Huang and Christ, 2000;Kahane et al, 1998b;Kahane et al, 2002) that intercalate among a scaffold of earlier pioneer fibers and depend on integrity of this scaffold for proper patterning (Kahane et al, 1998a;Kahane et al, 2007). Similarly, progenitors delaminate from the central DM sheet and generate differentiated myocytes (Ben-Yair et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Cdo ectodomain does not interact with itself in trans and has no obvious adhesive properties, but it binds several proteins as a putative coreceptor (9,(11)(12)(13)(14). In myoblasts, Cdo forms cis complexes with the cell-cell adhesion molecule N-cadherin (Ncad) (11), which is itself promyogenic (15)(16)(17)(18)(19)(20). Cell-cell contact stimulates myoblast differentiation, and although Ncad is not essential for myogenesis (likely due to redundancy with other cadherins) (21), direct Ncad ligation can substitute for cell-cell contact to enhance muscle-specific gene expression and myoblast differentiation (17,19).…”
mentioning
confidence: 99%